Interactive E-Modules: Revolutionizing English Learning for University Students in the IR 4.0 Era - Sujarwo, Sujarwo; Sukmawati, Sukmawati; Asdar, Asdar (Linguistics and ELT Journal, 2024)
The world is presently undergoing a fourth industrial revolution. Artificial intelligence, supercomputers, genetic engineering, nanotechnology, autonomous transportation, and innovation. This study investigated the impact of an interactive E-module as an innovative English learning tool for D3 Dental Engineering students during the Industrial Revolution 4.0. This study employed a quasi-experimental methodology, incorporating both experimental and control groups. The sample consisted of 56 students, including first-semester students from the D3 Dental Engineering and D3 Midwifery programs, totalling 28 students. The findings demonstrated that the implementation of interactive E-modules as an innovative approach to English learning during the Industrial Revolution 4.0 era had a significant effect, as evidenced by the higher average posttest score of D3 Dental Engineering students (M = 72.86; SD = 10.752) compared to that of D3 Midwifery students (M = 63.75; SD = 12.143). Implementing an interactive E-module significantly influences English learning outcomes for first-semester students. This research emphasizes the necessity of interactive E-modules as an innovative approach to students in the context of the Fourth Industrial Revolution, highlighting the need for more effective learning methods. The implication of interactive e-module is digitally delivered learning materials designed to enhance engagement and interactivity.